Measuring barriers to access financial services in East Java, Indonesia: A confirmatory factor analysis (CFA) - Abdul Razak, Dzuljastri; Maulana, Hartomi; Adewale, Abideen Adeyemi (International Journal of Business Economics and Law, 2017)
Even though the banking industry is growing exponentially, they are still out of reach of the hardcore poor. The population under poverty remains financially excluded from the mainstream banking facilities. The aim of this paper is to empirically examine the main factors that hinder customers to access financing from mainstream banking in Indonesia’s province of East Java using confirmatory factor analysis (CFA). The paper employs primary data collected by self-administered questionnaires involving a sample of 243 respondents from five different regencies in East Java. A CFA techniques were used on the hypothesized model with five latent variables, namely religious, affordability, accessibility eligibility, availability factors. The result reveals that the goodness-of-fit indices are adequate with the hypothesized model using the fit indices criteria. Hence, it can be concluded that the five variables mentioned above are indeed factors that contribute to financial exclusion of micro enterprenuers in mainstream banking in East Java, Indonesia. The result would be beneficial to practitioners and policymakers on factors that are important for the financial needs of the microenterprenuers which represent the highest portion of Micro Small and Medium Enterprises (MSMEs) in Indonesia.